The Myth of the State - Cassirer, Ernst 1874-1945 (London New Haven, CT Yale University Press, 1975)
A great contemporary German philosopher attacks the explosive problem of political myth in our day, and reveals how the myth of the state evolved from primitive times to prepare the way for the rise of the modern totalitarian state. "A brilliant survey of some of the major texts in the history of political theory."Kenneth Burke, The Nation
Keywords: 20th Century (1901-2000); Philosophy; Politics; Germany